Strength, extent and duration of secondary hyperalgesia induced by high-frequency electrical stimulation of the foot compared to the volar forearm of healthy human volunteers - Lebrun, Louisien; Lenoir, Cédric; Leone, Caterina; Broeke, Emanuel N. van den; Caspani, Ombretta; Schilder, Andreas; Pelz, Bernhard; Truini, Andrea; Treede, Rolf-Detlef; Mouraux, André (PLOS ONE, 2025)
High-frequency electrical stimulation (HFS) of the skin using a multi-pin electrode activating epidermal nociceptors is used to explore spinal central sensitization in humans. Most previous studies applied HFS to the volar forearm. To prepare for clinical applications in which HFS could be applied to different body sites, this study compared the secondary hyperalgesia induced by stimulation of the foot dorsum vs. the forearm in 32 healthy volunteers. HFS consisted in five 1-s trains of 100 Hz pulses (inter-train interval: 10 s; intensity: 20x detection threshold) delivered via a novel electrode optimized for stimulation of different body sites (ten 0.25 mm pins in a 5-mm circle). Pinprick sensitivity was assessed before HFS and 30-240 minutes after HFS, at the treated site and the corresponding contralateral site. The area of hyperalgesia was quantified. HFS to the foot induced a significant increase in pinprick sensitivity of the surrounding skin, similar in magnitude to the increase at the forearm, and decaying similarly over time (half-lives 150 vs. 221 min). The radius of secondary hyperalgesia was smaller at the foot (22 mm) compared to the forearm (38 mm, p < 0.001), and decreased more rapidly over time (53 vs. 87 min, p < 0.01). Our results show that strength of HFS-induced secondary hyperalgesia can be used as indicator of spinal central sensitization across body sites, and thereby profile patients with localized or regional pain conditions. The size of the area of hyperalgesia may depend on innervation density and peripheral receptive field sizes.
Gesehen am 15.07.2025